Black college students at elevated risk for suicide: Barriers to mental health service utilization. Issue 3 (3rd April 2021) - Busby, Danielle R.; Zheng, Kai; Eisenberg, Daniel; Albucher, Ronald C.; Favorite, Todd; Coryell, William; Pistorello, Jacqueline; King, Cheryl A.
Abstract: Objective: To examine differences between Black students who do and do not screen positive for suicide risk; to describe barriers to mental health service utilization (MHSU) among participants with a positive screen and no current MHSU and; to determine if barriers vary by student characteristics. Participants: 1, 559 Black students (66% female), ages 18 years and older ( M  = 21 years, SD  = 2.61) recruited from September 2015 to October 2017 across four universities. Method: Participants completed an online survey assessing demographics, suicide risk, MHSU, and barriers to MHSU. Results: Seventeen percent of students screened positive for risk; 66% of these students were not receiving MHS. Students who screened positive were female and younger. Perceived problem severity (74%) was reported most frequently. Conclusions: Efforts to improve MHSU among Black college students at risk for suicide should address students' awareness of treatable MH problems and time concerns.